Optimization of Raw Material Inventory Management and Productivity Analysis in Small-Scale Fish Milling Business: A Case Study of Afif Tenggiri Bengkulu: Raw Material Inventory Management Analysis - Indah Purnawan; Rika Dwi Yulihartika ; Herri Fariadi (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: Afif Tenggiri Bengkulu, a fish milling business, faces challenges in raw material inventory management due to irregular frequency and delivery delays, especially during the rainy season. This research analyzes raw material inventory management and productivity at Afif Tenggiri in Bengkulu City. Methodology: Conducted in Kampung Bahari, RT 14 Pulau Baai, from April to May 2025, using direct observation and interviews with the owner. Results: Results show effective inventory management through planning, organizing, mobilizing, and controlling stages. EOQ calculations yield optimal order quantity of 441.31 kg, Safety Stock of 5,331 kg, and reorder point of 10,662 units. Productivity: raw materials 0.4 (moderate), labor 40.92 kg/person/month (moderate), operational cost 6.59787 kg per Rp 1,000,000 (moderate). Findings: The findings indicate that inventory management is well-executed, yet productivity remains at moderate levels across all measured dimensions. Novelty & Originality: The novelty of this study lies in its application of EOQ-based inventory analysis to a small-scale fish milling business in Bengkulu, a context rarely examined in prior research. Conclusions: The study recommends improving supply chain coordination and operational efficiency to enhance overall productivity. Type of Paper: This paper is an case study research paper.